Association Between Dietary Phytochemical Index and Neonatal Thyroid Function - Vida Hashemi Dehkordi; Mehri Khoshhali; Motahar Heidari-Beni; Elham Hashemi Dehkordi; Mahin Hashemipour; Neda Mostofizadeh; Seyede Shahrbanoo Daniali; Roya Kelishadi (Hindawi Limited, 2024)
Conclusion: No significant relationship between maternal DPI with cord serum TSH and FT4 levels was shown. Limited experience exists about the effect of maternal diet quality indices on neonatal thyroid function, and further studies are needed in this regard.